The influence of adversity quotient and job stress on employee performance through work motivation as an intervening variable (Study of conventional taxi drivers in Medan City) - Lubis, Anggia Sari (MEC-J (Management and Economics Journal), 2019)
This study aims to examine and analyze the influence of adversity quotient (measured through control, origin, reach and endurance), and work stress (measured through roles in the organization, workload, career development, employee relations, and organizational climate), on employee performance through work motivation as an intervening variable of study in conventional taxi drivers in the city of Medan. The type of this research is associative research. The population in this study were 824 taxi drivers in Medan City. The sampling technique used was non probability sampling by convenience sampling method. The method of determining the number of samples is by looking at the Krecjie Morgan Table ,and the number of samples is 265 people. Testing of the research data using path analysis. The results of the study show that adversity quotient and work stress have a significant effect on job motivation and employee performance. According to the results of multiple regression analysis, there is a positive and significant influence between adversity quotient and employee motivation and employee performance, besides that the work stress variable has a positive and significant effect on work motivation, but has a negative and significant effect on performance. , it was found that adversity quotient and work stress had a direct influence on improving employee performance; In addition, the work motivation variable is not an intervening variable, because the adversity quotient and work stress variables can be directly related to the performance of conventional taxi drivers.